To Study the Mechanical Properties of Slag and Fly Ash Reinforced As 2024 Composites (International Journal of Innovative Research in Engineering & Management, 2022)
Metal matrix composites (MMCs) possess  significantly improved properties compared to  unreinforced alloys. There has been an increasing interest  in composites containing low density and low cost  reinforcements. In view of the generation of large  quantities of solid waste by products like fly ash and slags,  the present study is discarded, new methods for treating  and using these solid wastes are required. Hence,  composites with fly ash and Granulated blast furnace slag  as reinforcements are likely to overcome the cost barrier  for wide spread applications in automotive and small  engine applications. In the present investigation, AA 2024  alloy – 5 wt. % fly ash and slag composites separately were  made by stir casting route. Phase identification and  structural characterization were carried out on fly ash and  GBF slag by X-ray diffraction studies.The hardness and  compression tests were carried out on all these alloy and  composites. The reinforcement Improved hardness and  mechanical properties were observed for both the  composites compared to alloy; this increase is higher for  AA2024-Fly ash composite than AA2024- Granulated  blast furnace slag composite.
Keywords: Aluminium alloys; MMCs; Fly Ash; slag; Stir casting